Harnessing artificial intelligence for enhanced nanoparticle design in precision oncology - Mujibullah Sheikh; Pranita S. Jirvankar (AIMS Bioengineering, 2024)
The integration of artificial intelligence (AI) with nanoparticle technology represents a transformative approach in precision oncology, particularly in the development of targeted anticancer drug delivery systems. In our study, we found out that the application of AI in the field of drug delivery enhances the value of nanoparticles in increasing the efficiency of drug delivery and decreasing side effects from specifically targeted mechanisms. Moreover, we considered urgent issues that exist in present-day nanoparticle fabrication such as scalability and regulatory issues and suggest AI solutions that would help overcome these issues. In the same manner, we focused on the utilization of AI in enhancing patient-centered treatment through the establishment of drug delivery systems that will complement the genetic and molecular makeup of patients. Additionally, we present evidence suggesting that AI-designed nanoparticles have the potential to be environmentally sustainable alternatives in cancer therapy. AI is presented as capable of creating synergies with bioengineering methods like CRISPR or gene therapy and able to show potential directions for enhancing the efficiency of nanoparticle-based cancer therapies. In implementing these findings, we systematically discuss and highlight ongoing work and potential development trends in AI-aided nanoparticle research, asserting that it has the potential to greatly enhance oncology therapy.